Resistant starch reduces large intestinal pH and promotes fecal lactobacilli and bifidobacteria in pigs. (10th May 2018) - Metzler-Zebeli, B. U.; Canibe, N.; Montagne, L.; Freire, J.; Bosi, P.; Prates, J. A. M.; Tanghe, S.; Trevisi, P.
Abstract : Dietary resistant starch (RS) may have prebiotic properties but its effects on fermentation and the microbial population are inconsistent. This meta-analysis aimed to quantify the relationship between RS type 2 (RS2) and intestinal short-chain fatty acids (SCFA) and pH as well as certain key bacterial taxa for intestinal health in pigs. From the 24 included articles with sufficient information about the animal, and dietary and physiological measurements published between 2000 and 2017, individual sub-data sets for fermentation metabolites, pH, bacterial abundances and apparent total tract digestibility were built and used to parameterize prediction models on the effect of RS2, accounting for inter- and intra-study variability. In addition, the effect of pig's BW at the start of the experiment and duration of the experimental period on response variables were also evaluated using backward elimination analysis. Dietary RS levels ranged from 0% to 78.0% RS, with median and mean RS levels of 28.8% and 23.0%, respectively. Negative relationships could be established between dietary RS and pH in the large intestine ( P <0.05), with a stronger effect in the mid and distal colon, and feces ( R 2 =0.64 to 0.81; P <0.001). A dietary level of 15% RS would lower the pH in the proximal, mid-, distal colon and feces by 0.2, 0.6, 0.4 and 0.6 units, respectively. Increasing RS levels, however, did not affect SCFA concentrations in the hindgut, but enhanced the molar proportion of propionate in mid-colon and reduced those of acetate in mid-colon and of butyrate in mid- and distal colon ( R 2 =0.46 to 0.52; P <0.05). Backward elimination indicated an age-related decrease in mid-colonic propionate proportion and increase in mid- and distal colonic butyrate proportion ( P <0.05), thereby modulating RS2 effects. In feces, increasing RS levels promoted fecal lactobacilli ( R 2 =0.46; P <0.01) and bifidobacteria ( R 2 =0.57; P <0.01), whereby the slope showed the need for a minimal RS level of 10% for a 0.5 log unit-increase in their abundance. Best-fit equations further supported that a longer experimental period increased fecal lactobacilli but decreased fecal bifidobacteria ( P <0.05). In conclusion, dietary RS2 seems to effectively decrease digesta pH throughout the large intestine and increase lactic acid-producing bacteria in feces of pigs which may limit the growth of opportunistic pathogens in the hindgut. To achieve these physiologically relevant changes, dietary RS should surpass 10% to 15%.